2007
DOI: 10.1210/jc.2006-2896
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition in Children and Adolescents Born afterin VitroFertilization or Spontaneous Conception

Abstract: Our observations indicate that body fat composition in IVF children is disturbed. Follow-up of IVF children to monitor body fat pattern and potentially related health problems from adolescence into adulthood is of great importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
127
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 37 publications
5
127
0
11
Order By: Relevance
“…The data described in this paper were derived from a large study performed between March 2003 and March 2006 on the growth, health, and psychological functioning of IVF children born between 1986 and 1995 (see for more details of the study population Ceelen et al [5]). Families with a singleton child conceived by IVF conception in the VUmc, Amsterdam, the Netherlands, were invited by mail to participate in the study.…”
Section: Population and Participantsmentioning
confidence: 99%
“…The data described in this paper were derived from a large study performed between March 2003 and March 2006 on the growth, health, and psychological functioning of IVF children born between 1986 and 1995 (see for more details of the study population Ceelen et al [5]). Families with a singleton child conceived by IVF conception in the VUmc, Amsterdam, the Netherlands, were invited by mail to participate in the study.…”
Section: Population and Participantsmentioning
confidence: 99%
“…The authors conclude that ART children display generalized vascular dysfunction and that these are related to the ARTprocedure [79,82].…”
Section: Norwegian Data On Art Children and Their Siblingsmentioning
confidence: 94%
“…IVF and ICSI are also suggested to change the early environment in such a manner that it may have long-term consequences for the offspring (21). Indeed, several studies suggested subtle cardiometabolic alterations in IVF/ICSI offspring (5,6,8,9). This was partly expected, as IVF and ICSI conceptions more often result in preterm birth and low birth weight, which are risk factors for adiposity and hypertension (22).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the health outcome of children born following PGS. In this respect, it is noteworthy that recent reports indicated that IVF/ICSI by itself is associated with increased blood pressure (BP), altered body fat distribution, and vascular dysfunctions in offspring (5)(6)(7)(8)(9). Taking into account the general notion that the early environment shapes an individual's physical health later in life (10), it is conceivable that PGS, which includes more extensive embryo manipulation, introduces extra risks for adverse cardiometabolic outcome in offspring.…”
mentioning
confidence: 99%